A Complex of Marine Geophysical Methods for Studying Gas Emission Process on the Arctic Shelf - Artem A. Krylov; Roman A. Ananiev; Denis V. Chernykh; Dmitry A. Alekseev; Ermolay I. Balikhin; Nikolay N. Dmitrevsky; Mikhail A. Novikov; Elena A. Radiuk; Anna V. Domaniuk; Sergey A. Kovachev; Georgy K. Timashkevich; Vladimir N. Ivanov; et al. (Sensors, 2023)
The Russian sector of the arctic shelf is the longest in the world. Quite a lot of places of massive discharge of bubble methane from the seabed into the water column and further into the atmosphere were found there. This natural phenomenon requires an extensive complex of geological, biological, geophysical, and chemical studies. This article is devoted to aspects of the use of a complex of marine geophysical equipment applied in the Russian sector of the arctic shelf for the detection and study of areas of the water and sedimentary strata with increased saturation with natural gases, as well as a description of some of the results obtained. This complex contains a single-beam scientific high-frequency echo sounder and multibeam system, a sub-bottom profiler, ocean-bottom seismographs, and equipment for continuous seismoacoustic profiling and electrical exploration. The experience of using the above equipment and the examples of the results obtained in the Laptev Sea have shown that these marine geophysical methods are effective and of particular importance for solving most problems related to the detection, mapping, quantification, and monitoring of underwater gas release from the bottom sediments of the shelf zone of the arctic seas, as well as the study of upper and deeper geological roots of gas emission and their relationship with tectonic processes. Geophysical surveys have a significant performance advantage compared to any contact methods. The large-scale application of a wide range of marine geophysical methods is essential for a comprehensive study of the geohazards of vast shelf zones, which have significant potential for economic use.